Perencanaan Madrasah Ibtidaiyah (MI) Swasta di Pedesaan dalam Menyelenggarakan Program Tahfiz Al-Qur`an - Ahmad Gawdy Prananosa; Donni Pestalozi; M. Rusni Eka Putra (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study was to determine the planning of private madrasah ibtidaiyah (MI) in rural areas in organizing the tahfiz al-qur'an program. This study uses a qualitative approach with phenomenological methods. This research was conducted in Madrasah Ibtidaiyah Assidiq Giriyoso, Jayaloka District, Musi Rawas Regency. The research subjects consisted of the Principal, the Board of Teachers, the Foundation. Data collection techniques include; observation, interviews and documentation, data analysis techniques using the interactive model of Miles and Huberman, where the analysis process is carried out simultaneously with the observation and interview processes and direct documentation is analyzed. The results of the study, it is very important to plan all components of the school in the success of the madrasa superior program, starting from student planning, curriculum, educators and education personnel, finance, and public relations, in planning activities can involve the community as an important element to support the progress of madrasas. Then the role of people's representatives can be used as a relationship or good relationship in advancing Madrasas. In conclusion, Madrasah Ibtidiayah Giriyoso has prepared supporting facilities such as the tahfiz cottage in front of the class, educators and education staff who are fluent and memorized the Koran, the curriculum listed in the learning implementation plan, then establish good relations with the community, especially in supporting school programs. Keywords: Planning, Tahfiz Qur'an Program, Madrasah Ibtidaiyah